Ammonia stress on the carbon metabolism of Ceratophyllum demersum. (27th February 2015) - Gao, Jingqing; Li, Linshuai; Hu, Zhiyuan; Zhu, Songfeng; Zhang, Ruiqin; Xiong, Zhiting
Abstract: In the present study, carefully controlled pH ranges (7 and 9) were used to distinguish between the effects of un‐ionized NH3 and the NH4 + ion. The objective was to find the effect of different total ammonia nitrogen concentrations and pH values on the carbon metabolism of Ceratophyllum demersum . The authors investigated the effects of ammonia on the nonstructural carbohydrate content in shoots of C. demersum . Ammonia treatment decreased the contents of nonstructural carbohydrate, soluble sugar, sucrose, fructose, and starch in leaves. Meanwhile, increasing the pH value exacerbated the decline of the C. demersum nonstructural carbohydrate content. In addition, the activity of invertase was increased during the experiment. These results suggest that ammonia severely inhibits plant growth by disturbing nonstructural carbohydrate content. It has been suggested that ammonia has toxic effects on C. demersum and that the higher the pH in water, the more obvious the physiological responses that C. demersum exhibits. The results of the present study can provide some reference for studying the living conditions of submersed macrophytes under the stress of NH3 . Environ Toxicol Chem 2015;34:843–849. © 2014 SETAC